2000
DOI: 10.1038/sj.ejhg.5200568
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of three HIV-1 resistance-conferring polymorphisms (SDF1-3′A, CCR2-64I, and CCR5-Δ32) in global populations

Abstract: Chemokine receptors (CCR5, CXCR4 and CCR2) have been shown to be important co-receptors for HIV infection. Mutations at CCR5 (CCR5-∆32), CCR2 (CCR2-64I), and stromal-derived factor SDF1 (SDF1-3'A), a primary ligand for CXCR4, are known to have protective effects against HIV-1 infection and the onset of AIDS symptoms. We studied the three-locus genotype frequency distributions in 70 worldwide populations from a sample of 2341 individuals without any known history of HIV-1 infection and AIDS symptoms. From these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
53
2
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 20 publications
15
53
2
4
Order By: Relevance
“…It has been found in high frequencies in Oceania and in lower frequencies in Africa (Su et al 2000). In Brazil, Grimaldi et al (2010), studying the same three populations that were analysed by Acosta et al (2003) for CCR2-64I, found an allelic frequency of 21% in the population of the South, similar to the frequency found in this study (20.1%).…”
Section: Discussionsupporting
confidence: 86%
“…It has been found in high frequencies in Oceania and in lower frequencies in Africa (Su et al 2000). In Brazil, Grimaldi et al (2010), studying the same three populations that were analysed by Acosta et al (2003) for CCR2-64I, found an allelic frequency of 21% in the population of the South, similar to the frequency found in this study (20.1%).…”
Section: Discussionsupporting
confidence: 86%
“…Amongst the seropositive individuals the frequency was higher at 48 % though the difference was insignificant. Frequency of 48 and 24 % amongst a diverse population in Andhra Pradesh [18] and Northern India [26] respectively were recorded in [9,23]. We recorded only heterozygous mutants for CCR2-64I alleles.…”
Section: Discussionmentioning
confidence: 98%
“…A synergistic protective effect in individuals carrying SDF1-3'A and CCR2-64I would be consistent with this model. The SDF1-3'A allele is widely distributed, and has particularly high frequencies in Oceania, especially in New Guinean Highlanders (up to 72%), but is less common (3% to 12%) in African populations and has been found with frequencies between 15% and 22% in Europeans (Su et al, 1999(Su et al, , 2000. In urban Brazilian populations not tested for HIV infection the SDF1-3'A allele was found at frequency of 0.223 in the population of Belém (Carvalhaes et al 2004).…”
mentioning
confidence: 97%
“…In Brazilian urban populations (HIV serological status not determined) the CCR5 variant has been found with frequencies between 0.030 and 0.065 (Passos and Picanço, 1998;Pereira et al, 2000;Munerato et al, 2003;Carvalhaes et al, 2004). This mutation is rare in Afro-Brazilians communities (0.008) and absent in Brazilian Amerindians (Leboute et al, 1999;Su et al, 2000;Grimaldi et al, 2002;Carvalhaes et al, 2004). Smith et al (1997) states that CCR2-64I is a G to A substitution that results in the replacement of valine with Genetics and Molecular Biology, 28, 4, 665-669 (2005) Copyright by the Brazilian Society of Genetics.…”
mentioning
confidence: 99%
See 1 more Smart Citation